Development of celiac-safe foods: prevention of transglutaminase 2 (TG2) deamidation of gluten in healthy non-celiac volunteers - Engström, Niklas; Böhn, Lena; Josefsson, Axel; Störsrud, Stine; Scheers, Nathalie (Frontiers in Nutrition, 2024)
In celiac disease, intestinal transglutaminase (TG2) produces immunogenic peptides by deamidation of gluten proteins. These products drive the celiac immune response. We have previously identified an interaction between gliadin and a food additive, E304i, which prevents gliadin processing (both deamidation and transamidation) by TG2, in vitro. Here we investigated if E304i could prevent TG2 processing of gluten in flours and if the effect was evident after simulated gastrointestinal digestion. We also confirmed the outcome in vivo in a human cross-over intervention study in healthy nonceliac participants. TG2 transamidation experiments (in vitro) of digested wheat and rye flours supplemented with E304i at 30 mg/g indicated full prevention of TG2 processing. In the intervention study, participant serum levels of deamidated gliadin peptides (dGDP) increased after intake of reference wheat rolls (80 g a day for a week; 41% ± 4% compared to washout), whilst intake of the intervention E304i/zinc sulphate wheat rolls generated a modest response (80 g a day for a week; 8% ±10 % of control). The difference between the groups (32.8% ±15.6%) was significant (p=0.00003, n=9), confirming that E304i /zinc addition to wheat rolls prevented TG2 deamidation of gluten. In conclusion, this study shows that E304i /zinc addition to wheat rolls prevents TG2 deamidation of gluten in non-celiac participants.